EXAMINING THE DESIGN PARAMETERS FOR BALCONY IN MUSLIM SUDANESE APARTMENTS WITH A VIEW TO ENHANCE SOCIAL INTERACTION AND VISUAL PRIVACY - Yousif, Maysa; Abdul Aziz, Aniza (International Journal of Property Sciences (E-ISSN: 2229-8568), 2023)
The balcony is considered an important element that makes valuable contributions to residential buildings at various levels, such as its function, use, design, and values. Balconies should be designed to improve the residential unit’s internal environment and be used for significant functions not only as a service area but also as a place for social interaction. Therefore, this study aims to analyse the balcony design variables that improve the degree of activity, privacy, interaction, and comfort for apartment unit residents, especially in Khartoum, where most of the population is Muslim. In order to evaluate the different variables and responses from residents, a mixed-method approach is used, combining questionnaire surveys and case study approaches. The findings revealed the significance of balcony space in Sudanese culture; also, respondents strongly support the idea that balconies might replace the function of traditional house yards if they evolve with a particular level of privacy and acceptable size. Hence, this paper provides design guidelines for balconies in apartment blocks that are suitable not only for the Sudanese but also the Muslims in general to preserve the good social culture.